Platelet Gene Therapy Promotes Targeted Peripheral Tolerance by Clonal Deletion and Induction of Antigen-Specific Regulatory T Cells - Luo, Xiaofeng; Chen, Juan; Schroeder, Jocelyn A.; Allen, Kenneth P.; Baumgartner, Christina K.; Malarkannan, Subramaniam; Hu, Jianda; Williams, Calvin B.; Shi, Qizhen (Frontiers in Immunology, 2018)
Delivery of gene therapy as well as of biologic therapeutics is often hampered by the immune response of the subject receiving the therapy. We have reported that effective gene therapy for hemophilia utilizing platelets as a delivery vehicle engenders profound tolerance to the therapeutic product. In this study, we investigated whether this strategy can be applied to induce immune tolerance to a non-coagulant protein and explored the fundamental mechanism by which immune tolerance induced by platelet-targeted gene delivery. We used ovalbumin (OVA) as a surrogate non-coagulant protein and constructed a lentiviral vector in which OVA is driven by the platelet-specific IIb promoter. Platelet-specific OVA expression was introduced by bone marrow transduction and transplantation. Control mice immunized with OVA generated OVA-specific IgG antibodies, however mice expressing OVA in platelets did not. Furthermore, OVA expression in platelets was sufficient to prevent the rejection of skin grafts from CAG-OVA mice. To assess the mechanism(s) involved in this tolerance we used OTII mice that express CD4+ effector T cells specific for an OVA-derived peptide. After platelet-specific gene transfer, these mice showed normal thymic maturation of the T cells cells ruling against central tolerance. In the periphery, tolerance involved elimination of OVA-specific CD4+ effector T cells by apoptosis and expansion of an OVA-specific regulatory T cell population. These experiments reveal the existence of natural peripheral tolerance processes to platelet granule contents which can be co-opted to deliver therapeutically important products.